[tex] \frac{2m}{2m+3} - \frac{2m}{2m-3} =1 \\ \frac{2m(2m-3)-2m(2m+3)}{4m^2-9} =1 \\ \frac{4m^2-6m-4m^2-6m}{4m^2-9} =1 \\ \frac{-12m}{4m^2-9} =1 \\ -12m=4m^2-9 \\ 4m^2+12m-9=0 \\ m=0.6213 \ or \ m=-3.6213[/tex]
For m = 0.6213, [tex]\frac{2(0.6213)}{2(0.6213)+3} - \frac{2(0.6213)}{2(0.6213)-3} \\ \frac{1.2426}{4.2426} - \frac{1.2426}{-1.7574} =0.2929+0.7071=1[/tex]
For m = -3.6213, [tex]\frac{2(-3.6213)}{2(-3.6213)+3} - \frac{2(-3.6213)}{2(-3.6213)-3} \\ \frac{-7.2426}{-4.2426} - \frac{-7.2426}{-10.2426} =1.7071-0.7071=1[/tex]
Therefore, the equation has no extraneous solution.